Young Adults’ Engagement with Facebook Advertisements : An Exploratory Study Using Theory of Planned Behaviour - Nandi, Shampa; Singh, Saumya (Indian Journal of Marketing, 2021)
Social networking sites have gained tremendous popularity and have become preferred media of communication, especially among young people. For the millennials and the generation Z, if any company is not online, it does not exist. This generation has grown up with smart phones and they are in full control of any media message they want to become exposed to. Among all of the social networking sites, Facebook has become the most common hangout platform for the young generation and has maintained its dominant position in the online space. Facebook allows companies to enhance customer interaction at a personal level and has huge opportunity to be one of the most viable advertising platforms. This paper examined the engagement level of young adults with Facebook advertisements using Ajzenâ€™s (1991) well known â€œtheory of planned behaviourâ€ model. Primary data were collected from college students and young professionals in the age group of 18â€“30 years. Structural equation modelling was performed to analyze the data through exploratory and confirmatory factor analysis. The study provided a strong support for the application of the TPB model for predicting young adultsâ€™ intention to engage with Facebook advertisements, but overall engagement of the viewers was found to be not very high.